Геоінформатика: історія становлення, предмет, метод, задачі (сучасна точка зору). Стаття XXV - Кулінкович, А.Є.; Якимчук, М.А. (Центр менеджменту та маркетингу в галузі наук про Землю ІГН НАН України, 2008)
Настоящая статья является двадцать пятой в серии публикаций, посвященных фундаментальным проблемам геоинформатики – предмет исследований и главные цели новой науки, методология получения результатов и т. д. В данной, двадцать пятой работе рассматриваются этапы научной революции в геологии и в смежных дисциплинах естествознания: 1) эмпирическая (фактографическая) революция; 2) теоретическая революция; 3) синтетическая революция. Специально анализируется «трансцендентальная революция», в основе которой лежит формализация Платоновой «парадигмальной идеи» (расшифровка «конституции Мироздания»). Как главный результат этой «трансцендентальной революции представлен для обсуждения онтологически корректный геохронологический календарь, который охватывает всю геологическую историю, являясь в то же время многоуровневым: включает эры, периоды, эпохи, века, полувека, фазы, полуфазы, кванты, полукванты. Продолжительность полукванта 343750 лет. Выявлен «феномен биогильотины», суть которого состоит в том, что происходит строго периодическое внезапное прекращение существования биологических видов с периодом 343750 лет. Соответственно, имеет место и периодичность биозон. In the sequence of publications the given twenty-fifth article demonstrates adherence to fundamental topics of geoinformatics: the subject matter of investigation, chief goals of a new science, strategic methods in the field of obtaining results, etc. This research work considers stages of scientific revolution both in geology and adjacent branches of natural sciences such as: 1). empirical revolution, relying on observation and experiment not theory; 2) theoretical revolution, based on theory, not on practice or experience; 3) synthetic revolution as a combination of separate parts, elements into a system; 4) transcendental revolution, going beyond human knowledge, experience or reason. The transcendental revolution is submitted to a special analysis that discloses in its backbone the Plato’s paradigmatic idea interpreting the Constitution of the Universe. The ontologically correct geological-chronological calendar as the most essential outcome of this revolution is presented for discussion. It encompasses the whole geological history being at the same time a multistage one, including eras, periods, epochs, ages, semi-ages, phases, semi-phases, quanta, semi-quanta. The longevity of a semi-quantum equals 343750 years. Consequently, the phenomenon of a “biological guillotine” has been exposed, the essence of which supports the fact of existing strictly recurrent sudden termination of existing biological species with the life period of 343750 years. The recurrence of biological zones takes place correspondingly.